Analysis of Digital Technology-Based Financial Management and Utilization of Financial Technology (FINTECH) in Micro, Small and Medium Enterprises Post-Covid-19 Pandemic in Pariaman City - Irni Yusnita; Sulastri Sulastri; Arivetullatif Arivetullatif (Enrichment : Journal of Management, 2022)
This study aims to analyze whether MSMEs in Pariaman City have implemented digital technology-based financial management and whether MSMEs in Pariaman City have utilized financial technology (fintech) as well as how financial management is and to what extent is the use of financial technology (fintech) in MSMEs in Pariaman City. The data in this study were taken through direct observation of MSME actors, interviews and distributing questionnaires to 99 respondents who are MSME actors or owners. The 99 respondents who were sampled from this study were calculated using the Slovin formula from a total of 8,840 SMEs as of January 2022 in Pariaman City. The questionnaires were distributed using the Guttman scale with two intervals, namely Yes and No. The results of this study indicate that the majority of MSMEs have not implemented good financial management digitally as seen from the indicators of budget planning, recording and reporting. As for the use of fintech, the majority of MSMEs have used fintech personally but have not used fintech in running their business.